1997
DOI: 10.1002/art.1780401213
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicenter, randomized trial comparing steroids and pulse cyclophosphamide versus steroids and oral cyclophosphamide in the treatment of generalized wegener's granulomatosis

Abstract: Objective. To investigate the effectiveness and side effects of oral versus pulse cyclophosphamide (CYC) in combination with corticosteroids (CS) in the treatment of systemic Wegener's granulomatosis (WG).Methods. Patients with newly diagnosed systemic WG were enrolled in a prospective, randomized trial. At the time of diagnosis, prior to randomization, every patient received a daily injection of methylprednisolone for 3 days, followed by daily oral prednisone (1 mg/kg/ day) and a 0.7-gm/m2 pulse of CYC. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
213
4
25

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(257 citation statements)
references
References 26 publications
10
213
4
25
Order By: Relevance
“…Furthermore, neither of these studies involved 4-OH-CPA measurements and the daily CPA doses used were rather high compared with the 50 mg/d commonly used in clinical trials that show antitumor activity of LDM CPA-based regimens (1, 3, 8 -14). Finally, our finding of maintained 4-OH-CPA levels and biological effects is in line with long-term beneficial effects of oral CPA protocols used for the treatment of immunologic disorders (38).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, neither of these studies involved 4-OH-CPA measurements and the daily CPA doses used were rather high compared with the 50 mg/d commonly used in clinical trials that show antitumor activity of LDM CPA-based regimens (1, 3, 8 -14). Finally, our finding of maintained 4-OH-CPA levels and biological effects is in line with long-term beneficial effects of oral CPA protocols used for the treatment of immunologic disorders (38).…”
Section: Discussionsupporting
confidence: 82%
“…According to a recently published retrospective analysis, it would appear that-for either disease-the addition of CY to CS benefits particularly patients presenting with factors of poor prognosis (4) and not for those without such signs (5). There is an ongoing controversy in the field of vasculitides whether CY should be administered orally (6,7) or intravenously (8,9). For PAN and MPA, prior studies suggested that an intermittent pulse-therapy may be as efficacious as oral CY at inducing remission (8,10) while generating fewer side effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients (perhaps 20-40%) appear to be "cured" by conventional therapy (2,6). However, disease flares following the tapering or discontinuation of treatment remain the rule, and treatment-induced side effects are a major source of morbidity and mortality (2,6,7).…”
mentioning
confidence: 99%